Snowball Throwing dalam Pembelajaran PAI Materi Puasa untuk Siswa Kelas VIII SMP N 8 Bintan - Ida Erniza (GHIROH, 2022)
This article focuses on applying the Snowball Throwing model in the learning of fasting in the Islamic Religion subject. This study aims to investigate the extent to which junior high school students in Bintan Regency can improve their learning outcomes in learning about fasting materials. The study used interview methods, observations, documentation and evaluation tests, and LKS (student worksheets) to answer these questions. Participants were students at a Junior High School in Bintan Regency, Kepulauan Riau. This study lasted for three months, where students were given actions in the form of pre-test and post-test. The results of the data analysis showed that students had learning outcomes that did not meet the KKM for learning before being given action but showed an increase in learning outcomes after experiencing the action. The results showed that the Snowball Throwing model's application became effectively used to improve learning outcomes.